Awareness and acceptance of contraception in post-partum women in a tertiary care hospital of Delhi - Singh, Meenakshi; Mehla, Suman; Ranjan, Rajesh; Das, Banashree (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: India is second most populous country of the world and in next few decades it will cross china if it will keep on increase by this exponential growth. This calls for steps to stabilize India’s population. India was the first country in the world to launch the Family Planning Programme in 1951. Despite this fact, India still lags behind in practicing contraception and limiting their family size. Methods: A prospective cross-sectional interview based study was conducted on a sample of 492 post partum women who underwent their deliveries in this hospital in six months duration in the department of Obstetrics and Gynecology, Safdarjung Hospital, New Delhi. The women were counseled regarding post-partum contraception after assessment of their knowledge and practices. The interview included socio demographic profile of the participants, their awareness for contraceptive methods and reasons for its acceptance/refusal. Results: Out of 492 post-partum women, 56.9 % accepted one of the contraceptive methods during their hospital stay only. The most common contraceptive method chosen was intrauterine device (45.0%). The main reason for non-acceptance of contraception was expectation of a male child. Conclusions: Providing effective, high quality antenatal and post-partum contraceptive counseling can reduce unintended pregnancies, decrease maternal and fetal morbidity and mortality and prevent unsafe abortions. In order to improve the situation, health authorities should be encouraged to provide counseling on postpartum contraceptive methods during antenatal and immediate postpartum period.